Taxonomic Diversity of the Fruit-feeding Butterflies (Lepidoptera: Nymphalidae) in Kubah National Park, Sarawak, Southwest Borneo - S.Gintoron, Christharina; Fatimah, Abang (Chulalongkorn University, 2014)
The diversity of nymphalid assemblages in primary, secondary and heath forests and forest edges in Kubah National Park, Kuching, was assessed by employing both conventional and taxonomic biodiversity indices. The lower variation in the taxonomic distinctness index (Λ+ ) in the primary forest indicated a distantly related array of nymphalids at a low taxonomic level, which is likely to be sustained by the numerous microhabitats. However, despite that the primary forest contained 74% of the total nymphalid species sampled in this study, the forest edge had the highest Λ+ , specifying speciose genera that were abundantly sampled in this habitat. Closer values of Λ+ between the secondary and heath forests and forest edges showed a resemblance in the taxonomic properties for these three assemblages, as having similar habitat requirements and ecological adaptations in their respective habitat. The utilization of taxonomic-based biodiversity indices inclusively leads to more meaningful findings and assists in diversity studies.